Analysis of Student Problem Solving Processes in Physics - Cicyn Riantoni; Rusdi; Maison; Upik Yelianti (International Journal of Education and Teaching Zone, 2023)
The main goal of learning physics is to understand physics concepts in-depth and apply them in the problem solving process. This article presents a synthesis of what students do when solving physics problems. The five topics discussed in this article consist of: (1) the difference between expert and novice in problem solving, (2) Physics Problem Solving Approach, (3) the use of examples in problem solving, and (4) the use of representation in physics problem solving. This article is the result of studies of problem solving research literature. Each topic section will be discussed related to the development of research results for each topic and problem solutions for future research. Although we do not limit the year as the reference source for this article, most of the reference sources are taken from the research of the last 20 years on solving physics problems.